"I Know It When I See It": Constructing Emotion and Emotional Labor in Social Justice News. Issue 5 (2nd September 2020) - Steinke, Allison J.; Belair-Gagnon, Valerie
ABSTRACT: This exploratory study examines the roles journalists rely on when covering social justice topics and what these role conceptions reveal about emotion and self expression values in news production. This article builds on Herbert Gans' definition of what news is, discursive understandings of journalistic performance, and emotion in news to understand and operationalize journalists' understandings of how their roles and reporting practices shape news coverage of social justice topics. Findings from qualitative interviews with journalists suggest that journalists that cover social justice topics seek to guide, motivate, and inspire audiences by utilizing emotion in the stories they choose to cover. Interview data shows that emotion and emotional labor are important components of the production of social justice news. This article adds to theoretical and practical understandings of how journalists who cover social justice topics discursively construct their professional roles, and how emotions contribute to a contemporary understanding of journalism and news.